Health and responsibility self-efficacy, self-care and self-responsibility - C. J. Eales; A. V. Stewart (AOSIS, 2001)
Self-care and self-efficacy have been discussed in the medical, psychological and sociological literature (Bandura, 1977b; Barofsky, 1978; Hickey, 1988; Mahler and Kulik, 1990; Mahler, 1991). However neither of these two concepts accurately describe the behaviour required of a patient with a chronic disease to ensure the best outcome of medical treatment. The concept of self-responsibility seems to be more appropriate. This article presents the definitions of self-efficacy, self-care and self-responsibility. An argument why self-responsibility is of importance in patients who have undergone bypass surgery will be presented. Coronary artery disease is a chronic disease, for which CABG is indicated only in special cases. The surgical intervention is costly and the operative outcome will not be successful if the patient does not comply with lifestyle and risk factor modification. In a climate where health costs are under scrutiny and attempts are being made to make the available funding accessible to a greater percentage of the population, there is a moral responsibility for patients who have undergone expensive interventions to accept the responsibility for their rehabilitation to ensure the optimal outcome of these interventions.